2011
DOI: 10.1007/s00402-011-1435-x
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Bernese osteotomy using three-dimensional computed tomography in hip dysplasia

Abstract: Computer-aided virtual surgery technique based on three-dimensional computed tomography information enabled acetabular coverage to be quantified preoperatively in Bernese osteotomy. Lateral rotation of osteotomized acetabular fragments improved anterior and posterior coverage as well as lateral coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It is difficult to obtain adequate acetabular coverage of the femoral head after PAO. In a virtual osteotomy study using CT images of the hips with acetabular dysplasia, Dong Hun Suh et al [19] suggested that when covering the femoral head, anterior displacement of the bone fragment is sometimes necessary in addition to lateral displacement. Siebenrock et al [20] reported that pincer FAI occurred in 29% of the cases they examined after PAO.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to obtain adequate acetabular coverage of the femoral head after PAO. In a virtual osteotomy study using CT images of the hips with acetabular dysplasia, Dong Hun Suh et al [19] suggested that when covering the femoral head, anterior displacement of the bone fragment is sometimes necessary in addition to lateral displacement. Siebenrock et al [20] reported that pincer FAI occurred in 29% of the cases they examined after PAO.…”
Section: Discussionmentioning
confidence: 99%
“…Among treatment methods for developmental dysplasia of the hip, RAO [1, 5, 6], ERAO [2] and periacetabular osteotomy [3, 4] are performed by resecting the acetabulum surrounding the femoral head, including acetabular cartilage, and displacement of the resected fragment laterally, thereby sufficiently covering the femoral head in order to prevent the progression of disease [16]. However, Dong Hun Suh et al [25] suggested that, in covering the femoral head, anterior displacement of the fragment of the bone is necessary in addition to lateral displacement in some cases, based on the virtual osteotomy using CT images of the hips with the acetabular dysplasia. Nevertheless, coverage of the femoral head by excessive anterior displacement may increase the incidence of postoperative FAI.…”
Section: Discussionmentioning
confidence: 99%
“…Proper acetabular reorientation is essential to avoid FAI after PAO, although the most important purpose of acetabular osteotomy is reorienting the acetabulum into a normal position [10]. Suh et al reported that only lateral rotation of the osteotomized acetabular fragments improved anterior coverage as well as lateral coverage [11]. Hamada et al also reported, in a three-dimensional (3D)-computed tomography (CT) simulation study, that only lateral rotation of the acetabulum to achieve a lateral center-edge (CE) angle of 30°resulted in larger anterior coverage than that of normal hips in half of the DDH cases, and a wide variation of anterior coverage was seen after lateral rotation of the acetabulum [12].…”
Section: Introductionmentioning
confidence: 99%